Kajian tentang teori-teori gender - Marzuki Marzuki (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Gender is a characteristic used as the basis for identifying the differences between men and women in terms of social and cultural conditions, values and behavior, mentality, emotions, and other non biological factors. To understand and resolve the issue of gender, we can stucfy various theories of gender. Gender theories adopted many of the theories of sociology and prychology;e.g. the stntcturalfunctional theory, social-corflict theory, theory of libera!feminism, theory of Marxistsocialist feminism, theory of radical feminism, ecofeminism theory, and theory of psychoanalysis.